MAGNETISM AND SUPERCONDUCTIVITY IN THE SPINEL SYSTEM LI-1-XMN-2+TI2O4, LI-1-XMG-2+TI2O4 - Lambert, P; Harrison, M; Edwards, P (1988)
X-ray powder diffraction measurements show that the M2+ cations substitute almost completely at the tetrahedral sites in the Li1-xMxTi2O4 spinel systems (M = Mn2+, 0 < x < 1; M = Mg2+, 0 < x < 0.2). The magnetic susceptibility of the Li1-xMxTi2O4 system is dominated by high-spin Mn2+ moments for x < 0.5 and shows ferrimagnetic ordering at low temperatures (15-55 K) for samples with higher x compositions. The occurrence of spontaneous magnetism in the Li0.4Mn0.6Ti2O4 sample is interpreted as indicating a compositionally induced metal-nonmetal transition near that composition. The titanium-titanium cation distance at the transition is 3.016(2) Å in excellent agreement with Good-enough's critical Rc value of 3.02 Å for Ti3+ ions. The magnetic susceptibility of the Li1-xMgxTi2O4 system is distinguished by large Pauli susceptibilities and the Curie behavior of small concentrations of spins trapped at defect sites. The superconducting transition temperature Tc falls with increasing x and shows a strong correlation with the lattice parameter in both series. A decreasing density of states at the Fermi level resulting from increasing electron correlation and electron-lattice interactions is proposed to account for these observations. Importantly, no magnetic impurity effect on Tc is observed. © 1988.